Effect of overhydration on time-trial swim performance - Maresh, C. M.; Bergeron, M. F.; Kenefick, R. W.; Castellani, J. W.; Hoffman, J. R.; Armstrong, L. E. (The Journal of Strength and Conditioning Research, 2001)
The effect of hydration status on performance has not been adequately emphasized or examined in swimmers. Theoretically, moderate overhydration might reduce the proportionate fluid loss from the circulation during exercise of this nature. To explore this issue, 11 (5 women, 6 men) collegiate swimmers swam 2 183-m (200-yd) time trials (3 days apart) in alternate, randomized euhydrated (EUH) and overhydrated (OH) states. Pre-exercise plasma osmolality (EUH: 288.5 ± 2.5 and OH: 284.6 ± 3.3 mOsmol·kg1; p < 0.001), urine specific gravity (EUH: 1.022 ± 0.003 and OH: 1.012 ± 0.003; p < 0.001), and body weight (EUH: 72.1 ± 9.3 and OH: 72.6 ± 9.2 kg; p < 0.01) values distinguished the two hydration states of the swimmers. There was no difference (p > 0.05) between hydration states in postexercise plasma osmolality (EUH: 312.8 ± 4.8 and OH: 307.2 ± 9.9 mOsmol·kg1), plasma volume (EUH: 16.5 ± 10.0 and OH: 17.7 ± 6.8 %), plasma lactate (EUH: 18.6 ± 3.6 and OH: 17.8 ± 3.4 mmol·11), heart rate (EUH: 167 ± 11 and OH: 166 ± 16 beats·min1), or perceived exertion (EUH: 16 ± 1 and OH: 16 ± 2) responses. Although performance time improved for 7 of the 11 swimmers during OH, there was not a statistically significant difference between the EUH (121.2 ± 8.1 seconds) and OH (120.8 ± 7.7 seconds) conditions. However, there was a modest bivariate correlation (r = 0.602; p < 0.05) between the change in body weight and change in performance time in going from the EUH to OH trials. These data demonstrated that overhydration provided no performance advantage for this group during a 183-m time-trial swim but emphasized the importance of adequate hydration in swim performance.